Antimycotic Activity of the Bacillus subtilis 534 Strain - Foundations of Probiotic Sporobakterin - N. I. Gabrielyan; I. V. Drabkina; T. B. Krupenio; M. V. Demyankova; I. A. Malanicheva; B. F. Vasilieva; T. A. Efimenko; I. G. Sumarukova; A. A. Glukhova; Yu. V. Boykova; N. D. Malkina; V. V. Udalova; et al. (Антибиотики и Химиотерапия, 2020)
The aim of the study was to find the antimycotic activity of the probiotic strain Bacillus subtilis 534 under conditions of in vitro cultivation. 36 clinical isolates of pathogenic fungi Candida albicans, C.catenulata, C.glabrata, C.krusei, C.lusitaniae, C.parapsilosis, C.tropicalis, Cryptococcus neoformans, Trichosporon sp. and algae Prototheca sp. were used as test items for the determination of antimycotic activity. Clinical isolates differ in resistance/sensitivity to antimycotics amphotericin, miconazole, ketoconazole, itraconazole, and fluconazole, with 10 clinical isolates resistant to all five of these drugs. Out of 36 clinical isolates, 34 are sensitive to the culture liquid of the strain B.subtilis 534 and the active components isolated from it. Presumably, in human intestine strain 534 forms antimicrobial compounds that are active against pathogenic fungi, which causes its antimycotic efficacy. The long-term use of Sporobacterin drug, which is a spore suspension of B.subtilis strain 534, in medical practice indicates no side effects.